Retrospective analysis of clinical and radiological outcomes of thoracolumbar vertebral fractures treated with monoplanar pedicle screws compared with fixed-axis and polyaxial screws - Duan, Wei; Zhao, Xin; Chang, Le; Sun, Zhen; Lai, Kangwei; Zhang, Jingchun; Tian, Buqi; Ye, Zhengxu (Frontiers in Medicine, 2025)
BackgroundPedicle screw fixation is widely utilized in thoracolumbar fractures to restore vertebral height and spinal alignment. Screw head design varies among fixed-axis (rigid), polyaxial (multiplanar mobility), and monoplanar (coronal mobility) types, impacting surgical outcomes. This study compares clinical and radiological outcomes of these screws.MethodsSeventy-five patients (2020–2024) with thoracolumbar fractures were divided into three groups: Group A (fixed-axis screws, n = 31), Group B (polyaxial screws, n = 19), and Group C (monoplanar screws, n = 25). Operative time, blood loss, radiographic parameters (anterior body compression index, vertebral body angle, regional Cobb angle), and Visual Analogue Scale (VAS) scores were assessed preoperatively, postoperatively, and at 3 and 12 months.ResultsGroup C (monoplanar) demonstrated significantly lower blood loss (64 ± 11.1 mL vs. 308.6 ± 88.8 mL, p < 0.05) and shorter operative time (88 ± 8.2 min vs. 158.9 ± 27.8 min, p < 0.05) than Group A, with no significant differences compared to Group B. Postoperative VAS improved across all groups (p < 0.05), though Group A had slightly higher scores. Radiographic correction loss occurred in all groups at 12 months (p < 0.05), but was more pronounced in Group B. No complications (infection, nerve injury) were observed.ConclusionMonoplanar pedicle screws, combining coronal mobility for minimally invasive placement and sagittal rigidity for stability, reduce blood loss and operative time compared to fixed-axis screws while maintaining comparable correction retention to polyaxial screws. These findings position monoplanar screws as a balanced option for thoracolumbar fracture fixation, optimizing minimally invasive benefits without compromising mechanical strength.